Analisis Prosedur BSM Gadai Emas Perspektif Se Bank Indonesia No.14/7/DPBS Dan Fatwa DSN MUI No. 26/DSN-MUI/III/2002 - Nidaul Izzah (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
Procedure Analyze of BSm Pawning (Rahn) Gold is in Compliance with SE Bank Indonesia perspective SE 14/7/DPbS and DSN MUI Fatwa No. 26/DSN-MUI/III/2002. BSM Pawning (Rahn) Gold is one of the products owned by PT. Bank Syariah Mandiri. A banking financial institution engaged in accordance with Islamic sharia system. This product has previously been carried out by the several institution by it self and it turned out that pawning is executed with conventional systems. Therefore, Bank Syariah Mandiri is trying to adopt this pledge into one of it is products through BSM pawning (Rahn) gold in accordance with Islamic sharia system.In conducting its business, Bank Syariah Mandiri has rules referenced by regulators which are Bank Indonesia as the regulator which regulates the banking processes and Majelis Ulama Indonesia (MUI) as the regulator of governing the rules of Islamic sharia. In carrying out any business process, Bank Syariah Mandiri should pay attention to the two regulators. That is the reason why the author feel the needs to conduct research on whether the procedure of BSM Pawning (Rahn) Gold is in compliance with Bank Indonesia perspective SE14/7/DPbS and DSN MUI Fatwa No.26/DSN-MUI/III/2002. This is necessary so that the authors feel confident to be able to become an agent in developing economy in accordance with Islamic sharia system.From the results of the analysis of this study, the writer found that the suitability of the product BSM Pawn (Rahn) Gold with the regulations from the two regulators. It is obtained from the questionnaire given to the customers of BSM Pawning (Rahn) Gold and from the interviews with employees of Bank Syariah Mandiri as the seller of the product. These results can also be the basis in learning the implementation of sharia economic system.